Creating Effective Communication in Educational Institutions: Case Study at SDIT Wadi Fatimah Kedawung Cirebon - Ade Like Rachmawati; Masduki Duriyat; Tamsikudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Effective communication is an essential element in the success of educational institutions. This research uses a qualitative case study research method (case study) conducted at SDIT Wadi Fatimah. Good communication between teachers, students, parents and other stakeholders can improve the quality of learning, build positive relationships, and create a conducive learning environment. The importance of effective communication in educational institutions and strategies that can be implemented to achieve it, effective communication can help improve student learning outcomes, build positive relationships between teachers and students, create a conducive learning environment, and increase cooperation between schools and parents. Some challenges that can hinder effective communication in educational institutions, such as differences in cultural backgrounds, language barriers, and lack of time to communicate, are some strategies that can be implemented to create effective communication in educational institutions, such as building positive relationships, questioning skills must be included in listening in effective communication without being irrigated. This abstract is expected to provide an idea of the importance of effective communication in educational institutions and the strategies that can be implemented to achieve it.